Stochastic models of glottal pulses from the Rosenberg and Liljencrants-Fant models with unified parameters. (September 2021) - Cataldo, E.; Bahiano, D.
Highlights: Stochastic models proposed to generate jitter. Stochastic models based on the Rosenberg model and the LF model unified. The variation of the glottal time interval modelled as a stochastic process. Generation of intelligible voiced sounds. Generation of voice signals with jitter and, consequently, hoarse voices. Abstract: In voice production the random variation of the glottal cycles in relation to a mean value caused by the (quasi-) periodic movement of the vocal folds generates the jitter phenomenon. Its study is important due to applications as identification of pathologies related to the voice, improvement of the naturalness of synthesized voices and calibration of signal processing algorithms to identify glottal cycles. The objective of this work is to build stochastic models for glottal signals, using the Rosenberg and Liljencrants-Fant models with unified parameters, and considering the glottal time interval as a random variable (total time from the opening up to the closing of the vocal folds in each cycle), simulating the situation where the stiffness of the vocal folds is a stochastic process. Four different models are proposed with generation of jitter phenomenon in glottal signals simulated. Intelligible voiced sounds are obtained, in the case of normal voices, signal with low level of jitter, and also in hoarse voices, when the levels of jitter are higher. All the sounds simulated are available to be listened.